Radiographic evaluation of preoperative periapical status in teeth with apical abscess - Chaudhary, Sanjeeb; Singh, Harender; Gharti, Archana; Chaudhary, Govind Kumar; Gupta, Abhishek (Journal of Kathmandu Medical College, 2023)
Background: The presence of preoperative periapical lesion is a significant prognostic factor that influences the outcome of endodontic treatment. Radiographic evaluation of periapical status is important for diagnosis, treatment, and prognosis of periapical lesion. Objectives: To radiographically compare and evaluate the preoperative periapical status using periapical index (PAI) in teeth with acute and chronic apical abscess. Methods: An analytical cross-sectional study was conducted in Chitwan Medical College, between 2022 February to 2022 May using nonprobability convenience sampling technique. Forty-eight periapical radiographs with a diagnosis of apical abscess 24 acute apical abscess (AAA) = Group 1; 24 chronic apical abscess (CAA) = Group 2) were included for evaluation. Four observers (Three endodontists and one oral radiologist) evaluated the periapical status on radiographs and scored them according to PAI scoring system. Statistical analysis was done using the Mann-Whitney U test and SPSS v.22. Results: The most common PAI score for teeth in Group 1 was three (13, 54.20%) with mean PAI score = 3.21 and in Group 2 the score was four (13, 54.20%) with mean PAI score = 3.79. Analysis of PAI scores found significant differences (p = 0.009, p <0.05) between groups. The distribution of PAI varied according to apical diagnosis (p <0.05). Intraobserver and Interobserver agreement values demonstrated good self-agreement and interobserver agreement. Conclusion: Teeth with CAA were more likely to have higher PAI scores and therefore, periapical radiograph and PAI scoring system can be used effectively for the evaluation of preoperative periapical status in teeth with apical abscess.